Circulating total 25(OH)D and calculated free 25(OH)D in professional academy footballers at a northerly latitude in the UK - Simon D. Bowles; Subhashis Basu; Mayur K. Ranchordas; Trevor Simper; Anthony Lynn (Termedia Publishing House, 2023)
There is limited data on the vitamin D status of UK-based professional academy footballers. Therefore, the objective of this study was to report total 25(OH)D, free 25(OH)D and free 1,25(OH) 2 D at the end of the winter (March) and summer periods (October) in a cohort ( n = 27) of professional academy footballers in northern England. Blood samples were collected to measure total 25(OH)D, parathyroid hormone, vitamin D binding protein, albumin and calcium. Free 25(OH)D and 1, 25(OH) 2 D were calculated. Dietary vitamin D intake and retrospective summer sunlight exposure were also collected. At the end of winter, 2/27 (7.4%) players were vitamin D deficient (25(OH)D 30 nmol/l < 50 nmol/l). By the end of summer, none were deficient but 3/14 (21.4%) were still insufficient. Median total 25(OH)D(82.2 nmol/l [IQR: 50.3-90.2] vs. 54.2 nmol/l [IQR: 36.8-71.9]; P = .02), free 25(OH)D (25.8 pmol/l [IQR: 15.1-33.1] vs. 13.2 pmol/l [IQR: 9.0-14.9]; P = .005) and free 1, 25(OH)2D (389 fmol/l [IQR: 209-594] vs. 212 fmol/l [IQR: 108-278]; P = .034) were significantly higher at the end of summer than the end of winter. At the end of winter, free 25(OH)D was lower (P = .003) in those vitamin D insufficient (8.8 pmol/l [IQR: 5.5-11.8]) vs. sufficient (13.7 pmol/l [IQR: 12.0 17.0]). There was a high prevalence of vitamin D insufficiency at the end of the winter. Free 25(OH)D was also lower at the winter timepoint and in players that were insufficient vs. sufficient.